2017
DOI: 10.1002/ijc.30609
|View full text |Cite
|
Sign up to set email alerts
|

Risk of high‐grade precancerous lesions and invasive cancers in high‐risk HPV‐positive women with normal cervix or CIN 1 at baseline—A population‐based cohort study

Abstract: Infection with high-risk human papillomavirus (HR-HPV) is transient and clears on its own in majority of the women. Only a few women who have persistent infection may finally develop cervical intraepithelial neoplasia (CIN) or cervical cancer in later years. The risk of progression in the HR-HPV-positive women with normal cervix or low-grade lesion on colposcopy and histopathology at baseline is less studied. We performed a longitudinal study on 650 HR-HPV-positive women with colposcopy and/or histopathology-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…We detected 48 HR-HPV-positive samples with apparent normal cytology, where 62.1% had multiple HR-HPV infections and 63.8% had a high viral load. A high viral load has previously been associated with the risk of persistent HPV infection [32]. We found that the patients with a persistent infection had a higher viral load at the time of the first sample collection, a finding that has been previously reported as a risk factor for persistent infection in other studies [33].…”
Section: Discussionsupporting
confidence: 83%
“…We detected 48 HR-HPV-positive samples with apparent normal cytology, where 62.1% had multiple HR-HPV infections and 63.8% had a high viral load. A high viral load has previously been associated with the risk of persistent HPV infection [32]. We found that the patients with a persistent infection had a higher viral load at the time of the first sample collection, a finding that has been previously reported as a risk factor for persistent infection in other studies [33].…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, among women <30 years with normal cytology there was a lower sensitivity for the HPV‐mRNA test (80%) compared to the HPV‐DNA test (89%). It is tempting to speculate that the difference in sensitivity may reflect transient HPV‐infections only detectable by the HPV‐DNA test, as transient HPV infections decrease with increasing age of women . However, our observation does not affect our main conclusion that HPV mRNA testing is appropriate for HPV primary screening programs which start for women ≥30 years of age …”
Section: Discussionmentioning
confidence: 69%
“…It is tempting to speculate that the difference in sensitivity may reflect transient HPV-infections only detectable by the HPV-DNA test, as transient HPV infections decrease with increasing age of women. 16 However, our observation does not affect our main conclusion that HPV mRNA testing is appropriate for HPV primary screening programs which start for women ≥30 years of age. 3 Both AIS and the usual types of ADC are aetiologically related to infection with HPV.…”
mentioning
confidence: 58%
“…In contrast, persistent infection with high risk (HR)-HPV, including HPV16 and HPV18, can be followed by the integration of viral DNA into the host cell genome [ 5 ]. The probability of having persistent HR-HPV infection augments progressively with higher viral load [ 12 ] and it is favored by E5, E6 or E7 activities permitting HR-HPV escape from host immune surveillance. In particular, both the E5 and E7 proteins of HR-HPV can impair major histocompatibility complex (MHC)-restricted presentation of viral peptides to cytotoxic or helper T lymphocytes [ 13 , 14 ].…”
Section: Role Of the Hpv-e5 E6 And E7 Proteins In The Developmentmentioning
confidence: 99%